2011
DOI: 10.1093/alcalc/agr019
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives among Spanish and Hungarian Young Adults: A Cross-National Study

Abstract: Despite the substantial differences in the drinking culture of both countries, drinking motives showed overwhelming similarities (e.g. rank order of motives and the particular relationships between motives and alcohol outcomes). Only few differences (e.g. Hungarian college students indicated a higher level of motives) were found in cross-national comparison. Our results imply that programs targeting risky drinking motives are likely to be successfully adapted to different drinking cultures in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
56
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 38 publications
10
56
1
4
Order By: Relevance
“…With an overall CFI of at least .95 and an SRMR of .034 and consistent with previous research (Kuntsche and Kuntsche, 2009;Mazzardis et al, 2010;Németh et al, 2011aNémeth et al, , 2011b, the results showed a good model fi t of the DMQ-R SF across age groups. It was only in some countries (e.g., Estonia and Portugal) that the model fi t was somewhat poorer.…”
Section: Factor Structuresupporting
confidence: 89%
See 2 more Smart Citations
“…With an overall CFI of at least .95 and an SRMR of .034 and consistent with previous research (Kuntsche and Kuntsche, 2009;Mazzardis et al, 2010;Németh et al, 2011aNémeth et al, , 2011b, the results showed a good model fi t of the DMQ-R SF across age groups. It was only in some countries (e.g., Estonia and Portugal) that the model fi t was somewhat poorer.…”
Section: Factor Structuresupporting
confidence: 89%
“…Only in the past few years have studies in a range of more diverse countries such as Great Britain (Atwell et al, 2011;Bruce et al, 2012), Germany (Wurdak et al, 2010), Hungary (Németh et al, 2011a;Urbán et al, 2008), Italy (Graziano et al, 2010;Mazzardis et al, 2010), the Netherlands (Crutzen and Kuntsche, 2013;SchellemanOffermans et al, 2011), Spain (Mezquita et al, 2011;Németh et al, 2011b), and Sweden (Comasco et al, 2010) investigated the structure of drinking motives and/or their links to alcohol-related outcomes. The evidence from these studies and from previous research is fairly consistent in that adolescents reported that they drank most often for social motives, followed by enhancement, coping, and conformity motives in that order (Cooper, 1994;Kuntsche and Kuntsche, 2009;Kuntsche et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the first goal of this collaboration is to examine the invariance of the four-factor structure of the measure of drinking motives (Cooper, 1994;Kuntsche & Kuntsche, 2009) across 10 nations. To date, the factor structure has been shown to be highly similar across all countries examined, including the United States, Brazil, Canada, Switzerland, England, Hungary, Australia, Spain, the Netherlands, Belgium, Denmark, Estonia, Finland, Ireland, Italy, Poland, Portugal, Scotland, Slovakia, and Wales (Crutzen & Kuntsche, 2012;Hauck-Filho, Teixeira, & Cooper, 2012;Kuntsche et al, 2014;Kuntsche, Stewart, & Cooper, 2008;Lyvers, Hasking, Hani, Rhodes, & Trew, 2010;Mazzardis, Vieno, Kuntsche, & Santinello, 2010;Németh et al, 2011). Only a handful of studies have directly compared the structure of motives across countries (Kuntsche et al, 2008;Kuntsche et al, 2014;Németh et al, 2011) and have found support for the invariance of the four-factor structure of drinking motives across the countries compared.…”
Section: Goals and Rationale Of Drincmentioning
confidence: 99%
“…A conscious decision to use or not to use alcohol is based on alcoholrelated expectations (Dai, Sternberg, 2004;Németh et. al., 2011).…”
Section: Introductionmentioning
confidence: 99%